Junk Food Consumption among High School Students in Iran: The Role of Food Advertising - Saeid Moradi Latreyi; Leila Mirhadyan; Afsaneh Pasha; Ehsan Kazemnezhad Leili (Journal of Holistic Nursing and Midwifery)
Introduction: Adolescence is one of the most important periods of human development. Nutrition plays an important role in health and prevention of disease during this period. Food advertising influences food purchase and food consumption among children and adolescents. Most of these advertisements are about the foods high in fat, salt and sugar. High exposure to these kinds of advertisements increases the tendency towards consuming junk foods in adolescents. Objective: This study aimed to determine the junk food consumption by the exposure to junk food advertisements among high school students. Materials and Methods: this analytical study with cross-sectional design, 341 students from public high schools in Rasht, north ofIran were selected by cluster random sampling method. Data were collected by a valid and reliable researcher-made questionnaire. The questionnaire was a self-report designed by the researcher which had two parts adapted from similar studies. The first part records demographic characteristics of students, and the second part assess the source and frequency of exposure to fast food/junk food advertisement and the frequency of fast food/junk food Consumption Data Analysis was performed using Kruskal-Wallis test at a significance level of 0.05. Results: Most of the subjects (52.2%) were female and in the 11th grade (37.2%). In terms of the frequency of exposure to junk food advertisement, 37.2%, 33. 4% and 15.3% of subjects reported “from time to time”, “quite often” and “very often”, respectively. Regarding the source of exposure tojunk food advertisement, 51.9% were exposed to more than one advertising source. The Kruskal-Wallis test results showed a significant difference in junk food consumption frequency based on the frequency of exposure to food advertisement (P=0.0001). Conclusion: High exposure to junk food advertisement can be associated with high consumption of junk foods and subsequently having chronic diseases in adulthood. Therefore, it is necessary to control the food advertising and provide a legal framework for supervising it.